Intrauterine lidocaine and naproxen for analgesia during intrauterine device insertion: randomized controlled trial - Shana M. Miles; Katerina Shvartsman; Susan Dunlow (BMC, 2019)
Abstract Background This study evaluates oral naproxen and intrauterine instillation of lidocaine for analgesia with intrauterine device (IUD) placement as compared to placebo. Methods This was a randomized, double-blind, placebo-controlled trial. Patients desiring levonorgestrel 52 mg IUD or Copper T380A IUD were randomized into treatment groups. Patients received either oral naproxen 375 mg or placebo approximately 1 h prior to procedure in conjunction with 5 mL of 2% lidocaine or 5 mL of intrauterine saline. The primary outcome was pain with IUD insertion measured on a visual analog scale immediately following the procedure. Prespecified secondary outcomes included physician pain assessment, post procedure analgesia, satisfaction with procedure, satisfaction with IUD, and pain assessment related to IUD type. Results From June 4, 2014 to October 28, 2016 a total of 160 women desiring Copper T380A or levonorgestrel 52 mg intrauterine device insertion and meeting study criteria were enrolled and randomized in the study. Of these, 157 (78 in the Copper T380A arm, 79 in the levonorgestrel 52 mg) received study treatment medication. There were 39 in naproxen/lidocaine arm, 39 in placebo/lidocaine arm, 40 in naproxen/placebo arm, and 39 in placebo/placebo arm. There were no differences in the mean pain scores for IUD placement between treatment groups (naproxen/lidocaine 3.38 ± 2.49; lidocaine only 2.87 ± 2.13; naproxen only 3.09 ± 2.18; placebo 3.62 ± 2.45). There was no difference in self-medication post procedure or in satisfaction with the procedure and IUD among women in the treatment arms or by type of IUD. Conclusion Naproxen with or without intrauterine lidocaine does not reduce pain with IUD placement. Clinical trial registration Clinicaltrials.gov, NCT02769247. Registered May 11, 2016, Retrospectively registered